Impact of elicitors and light on biosynthesis of sesquiterpene lactones in tissue culture of Arnica montana and its variety Arbo - Parafiniuk, Agata; Kromer, Krystyna; Fleszar, Mariusz G.; Wróblewska, Katarzyna; Wiśniewski, Jerzy Ł.; Gamian, Andrzej (Frontiers in Plant Science, 2025)
Arnica montana is a popular medicinal plant known for the sesquiterpene lactones (SLs) found in its flowers, which are valuable components in pharmacology and cosmetology. We present the application of in vitro culture of the species A. montana, representing the dihydrohelenalin type and Arbo variety, richer in helenalin, as an alternative to the flower plantations method for acquiring these metabolites. We specify culture conditions under which the SL content was determined using high-resolution liquid chromatography with quadrupole time-of-flight mass spectrometry (LC-QTOF-MS). On a basic Murashige and Skoog (MS) medium without growth regulators, an increase in light intensity within the 50–150 µmol m-2 s-1 positively stimulated SLs synthesis. A high content of SLs was confirmed in in vitro leaves of both species, particularly at the maximum tested light intensity of 150 µmol µmol m-2 s-1 (A. montana: 32.57 mg/g DW; Arbo variety: 73.90 mg/g DW). Chitosan, jasmonic acid (JA), and red light alter the spectrum of the present SLs, favoring helenalin derivatives. The study contributes to understanding light's intensity and spectrum in Arnica's leaf development process. It confirms the pivotal role of phytochrome in inducing the expression of GA biosynthetic genes that control trichome emergence and stimulate sesquiterpene lactones formation.